APPLICATION OF IMAGE FUSION TO IMPROVE QUALITY OF MULTISPECTRAL AERIAL PHOTOGRAPHY WITH UAV CASE STUDY: ITB JATINANGOR CAMPUS - Putra Ramadhani, Faisal
Image fusion is a process that combines high spatial resolution images with low spatial resolution multispectral imagery to obtain multispectral images with high spatial resolution. To meet these objectives methods were developed which were then tested on remote sensing satellites. With the development of aerial photography as a mapping method, knowledge of the best fusion methods for aerial photography is also needed. But the image fusion that is produced usually increases spatial resolution with side effect of reduced spectral resolution of the fused image. Therefore, a comparison of eight fusion methods is then tested based on the resulting pixel values to assess the suitability of the digital number of the image fusion results with the initial multispectral image. Fusion is performed on multispectral orthomosaic and normal orthomosaic which have better geometric accuracy. The comparison of pixel values use the results of Normalized Difference Vegetation Index (NDVI) calculation which then compared with the original multispectral image that has been transformed too. From the comparison, the best method that maintains the spectral resolution of aerial photography is Modified IHS.